THE EFFECTIVENESS OF THE BRITISH PARLIAMENTARY DEBATE TECHNIQUE (BPDT) TO ENHANCE THE STUDENTS’ SPEAKING PROFICIENCY - Gunawan; Rahmiati; Dewi Sartika (FKIP Unismuh Makassar, 2022)
This research objectives to know students' ability in speaking through the British Parliamentary Debate Technique (BPDT) and how the interest of students of University of Muhammadiyah Bone-in academic year 2021-2022 in speaking skill through the use of BPDT. This study uses a pre-experimental method. The data on the students’ speaking proficiency were collected through the use of BPDT and the students’ interest was measured by a questionnaire. The data acquired were then analyzed through descriptive and inferential statistics. The use of the British Parliamentary Debate Technique (BPDT) in classroom activities significantly improved the speaking proficiency achievement of English students of University of Muhammadiyah Bone. This is all based on the probability value (0.00) which shows it is smaller than the value of the significance level at (0.05).while the students' speaking interest aspect shows a high category based on the students' average score is 81.53